Automatic seepage detection in cable tunnels using infrared thermography. (3rd September 2019) - Lu, Zilin; Zhu, Fulong; Shi, Lang; Wang, Fengren; Zeng, Pengjun; Hu, Jianxiong; Liu, Xiaojian; Xu, Yixin; Chen, Qian
Abstract: Seepage in tunnel engineering, especially in underground cable tunnels, is one of the influencing factors in tunnel safety. Seepage directly or indirectly induces many tunnel accidents. The reliable observation and reasonable identification of seepage plays an important role in ensuring the safety of a tunnel. This paper introduces an infrared thermography-based auto-inspection system for seepage in cable tunnels. The leaks whether they are detectable visually or not are identified. The leakage area is accurately calculated to make a quantitative analysis. The objective assessment documents (in PDF format) are exported and the need for skilled inspectors is reduced. The results of the field trail indicate that the automatic detection system can greatly improve detection efficiency (the detection speed is increased by 2.67 times), save manpower (it needs only one or two inspectors using this detection system instead of four inspectors using the traditional method) and material resources, and improve tunnel safety, all of which are of great importance in tunnel engineering.